Srpske elite i velikosrpski nacionalistički projekat / Serbian Elites and The Greater Serbia Nationalist Project: Izgledi za raskid "organskog jedinstva" / Prospects for Breaking "Organic Unity" (Pregled: časopis za društvena pitanja / Periodical for social issues, 2022)
The paper presents a brief overview of the consequences of the actions of social elites in Serbia in terms of survival and nurturing of the nationalist course of society even after the disastrous results of the nationalist adventure of the 1990s, but also the interpretation seems to lead to its transformation. Social reality is still filled with a matrix of exclusive nationalism and chauvinism that is persistently created by political and intellectual elites leaving a narrow space for the actions of individuals and groups who would like a different social reality. The paper also presents some symbolic elements of the manifestation of the nationalist ideology of the Serbian elites, which aims to point out the deep connection between the elites and the consequences of their nationalist engagement. The prospects for their dissolution are emphasized through the necessary transformation of the value elements of society and the overthrow of the nationalist construct through deep democratization and the establishment of the rule of law. The author recognizes this path as a way of deconstructing the collectivist view of society about its own existence in an isolated and homogenized ethnic community that survives only in such circumstances. Slowly and painstakingly, the nationalist concept could be replaced by a civic and liberal one that emancipates a general community of individuals - a community that is peaceful on the inside and not a threat on the outside. The paper also points out that behind the nationalist activities of Serbian elites are often purely lucrative goals of individuals and groups with the aim of building, consolidating and gaining specific social positions, influence and wealth: some served nationalism "from profession and occupation", not out of conviction. This deep symbiosis is still obvious today and signals that social changes and the severance of their ties will be difficult, even if the leading political elites would sincerely want it.
Keywords: Social elites; nationalism; nationalist project; war crimes; revisionism; dealing with the past; chauvinism